A proposed audio-visual program for the Mindanao Institute of Technology - Pableo, Librada C.
The purpose of the study is to propose an audio-visual program for the Mindanao Institute of Technology. It looked into the practices and trends in the organization, establishment and administration, and the principles common to a college audio-visual program.